Effects of molecular interactions between the exposome and oxylipin metabolism on healthspan - Hinman, Jennifer; Alan, Jamie K.; Lee, Kin Sing Stephen (Frontiers in Physiology, 2025)
While aging is typically synonymous with the lifespan of an individual, the healthspan, or the total number of years an individual remains healthy and disease-free, is not necessarily related. A current, critical need in society has arisen as current populations are living longer than previous generations, thus increasing the number of people with age-associated diseases. However, the extent of all age mechanisms is not entirely known. Still, studies examining how the exposome, or an individual’s cumulative exposures throughout their life, can influence or modulate aging processes will strengthen our understanding of how to keep individuals healthy and disease-free longer, bridging the gap between lifespan and healthspan. In contrast, previous research has also demonstrated that the exposome impacts aging. One subcategory of the exposome, the specific external, encompasses daily exposures such as diet, lifestyle factors, and occupational and environmental exposures. In this review, we focus on the interactions between factors of the exposome, such as vitamins and minerals, and their effects on aging, cell death, cellular senescence, and unsaturated fatty acid metabolism. We also discuss the interaction between oxidative fatty acid metabolism and aging itself. Overall, understanding how various exposures impact both the oxylipin profile and healthy aging will inform future interventions aimed at improving the healthspan and quality of life for this large aging population.